Harnessing Economic Growth: Permaculture Farming in West Pesaman Regency: An Analytical SWOT Perspective - Nurhafiani Nurhafiani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to find out the strategy of development of the economic potential of permaculture agriculture in the district of West Pasaman. The method of analysis used is qualitative descriptive analysis through data collection using interview techniques. Then proceed with SWOT analysis to see the development strategy. The results of this study are the efforts of the landowners as well as the community in the development of the agricultural economic potential of the West Pasaman district through permaculture agriculture there is cooperation between the landowner and the local community with the aim of raising the economy of the community and the west Pasaman District has a huge potential in the agricultura sector based on SWOT analysis as a priority strategy on the strategy of SO (Strengths-Opportunities) is located in the Quadrant I with a value (positive, positive) with an IFE value of 1.66 and EFE of 1.6. The SO strategy has an enormous impact on the agricultural sector by leveraging its strengths and opportunities. The agricultural sector has become a prominent economic sector due to its very fertile soil characteristics with a tropical climate which makes it ideal for planting a variety of crops. The development of the agricultural sector is one of the prime programmes of the government so the government is paying great attention through agricultural development activities and the provision of capital assistance.